The Effect of Financial Literacy, Ease of Use and Brand Image of E-wallet on Consumptive Attitudes of Accounting Students: Pengaruh Literasi Keuangan, Kemudahan Penggunaan dan Citra Merek E-wallet Terhadap Sikap Konsumtif Mahasiswa Akuntansi - Pratama, Rizki Yudha; Abidin, Fityan Izza Noor (Indonesian Journal of Innovation Studies, 2022)
The purpose of this review is to analyze the effect of variable X (Independent) namely financial literacy, ease of use and brand image of e-wallet on variable Y (Dependent), namely student consumptive attitudes, with the help of SPSS version 26 application program. questionnaire as a data collection method that uses certain criteria in sampling. The sample of this study amounted to 71 respondents of accounting students at Muhammadiyah University of Sidoarjo. Then the analysis of data is tested to draw conclusions from the research that has been done. The conclusion of the study of the hypothesis using the partial test proves that the variables of financial literacy, ease of use and brand image of e-wallet have no effect on the consumptive attitude of accounting students at Muhammadiyah University of Sidoarjo. Likewise, the simultaneous test proves that together the variables of financial literacy, ease of use and brand image of e-wallet have no effect on the consumptive attitude of accounting students at Muhammadiyah University of Sidoarjo.